Q: -6 - 9a equals 16

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-21 = 9a - 15 - 3a -6 = 6a -1 = a

It is: 9a-a-a = 7a

a = 6b = 9a + b = 6 + 9 = 15

a= -0.8

If: 9a = 18b Then: a = 2b

Related questions

-a^2- 9a - 18 = 0 -(a^2 + 9a + 18) = 0 -(a + 6)(a + 3) = 0

-21 = 9a - 15 - 3a -6 = 6a -1 = a

It is: 9a-a-a = 7a

a = 6b = 9a + b = 6 + 9 = 15

a= -0.8

If: 9a = 18b Then: a = 2b

Collect like terms: 9a -7a = 9 - 15, ie 2a = -6, so a = -3

9a+21 3(3a+7)

2a+5a+9a = 16a

-14 + 9a = 389a = 52a = 52/9 or 5.78

12a + 6b + 9a + 14b =(12a + 9a) + (6b + 14b) =21a + 20b

10